Analysis of Problems and Solutions in Stakeholder Management in Digital Technology-Based Sustainable Construction Projects - Irika Widiasanti; Muhammad Rizki Rifandi; Mushab Hifzhul Haq; Keny Islam Nur Esa (Nucleus Journal, 2026)
Stakeholder management in modern sustainable construction projects faces significant complexity due to the diversity of priorities and barriers to the adoption of digital technology. A review of the literature indicates that there remains a significant gap regarding disagreements in decision-making, poor coordination between parties, and the sub-optimal use of technology at the project governance level. To address these issues, this research aims to formulate a comprehensive framework based on PMBOK 10 that integrates Multi-Criteria Decision Making (MCDM) with cutting-edge technologies (such as AI, blockchain, and fuzzy logic). This framework is designed to facilitate collaborative governance and enhance the effectiveness of aligning various interests throughout the project lifecycle. The research method uses a descriptive analysis approach to three main problem categories including stakeholder disagreements, digital technology evaluation, and stakeholder relationships. The research results identified nine specific problems with solutions based on Multi-Criteria Decision Making (MCDM), digital technology (AI, big data, blockchain), collaborative governance, and interactive stakeholder mapping systems. The discussion shows the importance of technology integration, human resource capacity building, communication transparency, and structured coordination mechanisms. The research conclusion confirms that effective stakeholder management requires a holistic approach that combines digital technology, participatory collaboration, and adaptive monitoring systems to improve the sustainability performance of infrastructure projects.